Peran Pendidikan Agama Kristen dalam mewujudkan Nasionalisme - Yudi Santoso; Yonatan Alex Arifianto (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2021)
Radicalism that occurs in Indonesia has started to enter the world of school education, such as fundamentalism based on religion which feels right, which threatens national harmony. Moreover, there are many serious problems that occur on social media with the aim of blaming the nation's leaders and there are also goals that are made to insult each other which pose a threat to national unity. The existence of Christian religious education is expected to answer the attitudes of believers, and the attitudes of students to have a spirit of nationalism. The author uses a literature research method with a descriptive qualitative approach, which can be concluded that the sense of nationalism is manifested by the understanding that is owned about nationalism which is connected in the submission of every believer to submit to God's Word. So that from this understanding there is an actualization for the attitude of nationalism. Furthermore, believers or students are also able to see in terms of the value of biblical truth about the attitude of nationalism from the perspective of the Christian faith. As well as the active role of Christian education and the spirit of nationalism, an obligation for believers to be carried out with an attitude of respect for the state, for others to continue to be poured into a lifestyle that upholds the attitude of nationalism that builds the nation. Abstrak Radikalisme yang terjadi di Indonesia sudah mulai masuk dalam dunia pendidikan sekolah seperti paham fundamental berdasarkan agama yang merasa benar berakibat mengancam kerukunan berbangsa. Terlebih banyak persoalan yang serius yang terjadi di media sosial dengan tujuan menyalahkan pemimpin bangsa dan juga ada tujuan yang dibuat untuk saling menghina yang menimbulkan ancaman bagi persatuan bangsa. Adanya pendidikan agama Kristen diharapkan dapat menjawab sikap orang percaya, dan sikap peserta didik untuk memiliki jiwa nasionalisme. Penulis menggunakan metode penelitian pustaka dengan pendekatan kualitatif deskriptif, yang dapat disimpulkan bahwa rasa nasionalisme diwujudkan dengan adanya pengertian yang dimiliki tentang nasionalisme yang terhubung dalam penundukan setiap orang percaya tunduk akan Firman Tuhan. Sehingga dari pengertian ini maka ada aktualisasi bagi sikap nasionalisme. Selanjutnya orang percaya atau peserta didik juga mampu melihat dari sisi nilai kebenaran Alkitabiah tentang sikap nasionalisme dari persepktif iman Kristen. Serta peran aktif pendidikan Kristen dan semangat nasionalisme suatu kewajiban orang percaya yang dijalankan dengan sikap menghormati negara, sesama untuk terus dituangkan menjadi gaya hidup menjunjung sikap nasionalisme yang membangun bangsa.